Decoupling control based on linear/non‐linear active disturbance rejection switching for three‐degree‐of‐freedom six‐pole active magnetic bearing. Issue 10 (1st July 2020) - Zhu, Huangqiu; Wang, Shaoshuai
Abstract : In order to decouple the three‐degree‐of‐freedom six‐pole active magnetic bearing (3‐DOF 6‐pole AMB) with strong couplings, non‐linear and multivariable, an linear/non‐linear active disturbance rejection switching control (L/NL‐ADRSC) strategy is put forward. Firstly, the configuration of the 3‐DOF 6‐pole AMB is presented, and the mathematics models of the radial and axial suspension forces are derived. Secondly, the advantages and disadvantages of linear active disturbance rejection control (LADRC) and non‐linear active disturbance rejection control (NLADRC) are analysed, and the L/NL‐ADRSC strategy is introduced. Thirdly, a L/NL‐ADRSC system is designed to realise the decoupling control for the 3‐DOF 6‐pole AMB, and a simple practical parameter design method is provided. Finally, the simulations and experiments are carried out to verify the effectiveness of the whole control system. The results show that the decoupling control effect of L/NL‐ADRSC is better than that of LADRC and NLADRC.